A novel heterojunction photocatalyst, Bi2SiO5/g-C3N4: synthesis, characterization, photocatalytic activity, and mechanism. Issue 47 (22nd April 2016) - Yang, Chin-Tsung; Lee, Wenlian William; Lin, Ho-Pan; Dai, Yong-Ming; Chi, Han-Ting; Chen, Chiing-Chang
Abstract : A new type of heterojunction photocatalyst, Bi2 SiO5 /g-C3 N4, was prepared using a controlled hydrothermal method. Abstract : A new type of heterojunction photocatalyst, Bi2 SiO5 /g-C3 N4, was prepared using a controlled hydrothermal method. The structure and morphology of the Bi2 SiO5 /g-C3 N4 photocatalyst were characterized by XRD, HR-TEM, FE-SEM-EDS, HR-XPS, FT-IR, PL, BET, EPR, and UV-Vis-DRS. The obtained Bi2 SiO5 /g-C3 N4 photocatalyst exhibits enhanced photocatalytic activity on the decolorization of crystal violet (CV) under visible-light irradiation. In particular, the catalytic performance illustrates the best reaction rate constant of 0.1257 h −1 using Bi2 SiO5 /g-C3 N4 as the photocatalyst, which is 5 and 3 times higher than the reaction rate constants of Bi2 SiO5 and g-C3 N4 as photocatalysts, respectively. This study shows that Bi2 SiO5 /g-C3 N4 can be used to suppress the recombination of photoinduced electron–hole pairs and contribute to the enhanced photocatalytic efficiency of semiconductors in the visible light-driven catalysis. The quenching effects of different scavengers, and EPR results demonstrate that the reactive O2 ˙ − plays the major role and ˙OH, h + and 1 O2 play minor roles in CV degradation. The probable photodegradation mechanisms are proposed and discussed.